2002
DOI: 10.1103/physrevd.66.083513
|View full text |Cite
|
Sign up to set email alerts
|

Construction of nonsingular pre-big-bang and ekpyrotic cosmologies and the resulting density perturbations

Abstract: We consider the construction of nonsingular Pre-Big-Bang and Ekpyrotic type cosmological models realized by the addition to the action of specific higher-order terms stemming from quantum corrections. We study models involving general relativity coupled to a single scalar field with a potential motivated by the Ekpyrotic scenario. We find that the inclusion of the string loop and quantum correction terms in the string frame makes it possible to obtain solutions of the variational equations which are nonsingula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 67 publications
4
174
0
4
Order By: Relevance
“…In string theory we have other non-perturbative and loop corrections such as the Gauss-Bonnet curvature invariant [31,32,36]. It is certainly of interest to extend our analysis to such a direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In string theory we have other non-perturbative and loop corrections such as the Gauss-Bonnet curvature invariant [31,32,36]. It is certainly of interest to extend our analysis to such a direction.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, there is a residual gauge freedom: a rescaling of the type ϕ → α ϕ, with α a positive number. The parameters of the scaling solutions change, accordingly, as Q → Q/α, λ → λ/α, β → β and formulas (32) and (34) are invariant under such a rescaling.…”
Section: A Kind Of Gauge Symmetrymentioning
confidence: 99%
“…Although these perturbations correspond to the ones which are generated before the bounce, it was shown that these spectra are preserved even long after the bounce if α ′ curvature and derivative corrections are taken into account [32]. The reason why the spectrum is highly blue-tilted is that the system is dominated by the kinetic energy of the scalar field.…”
Section: Einstein Framementioning
confidence: 99%
“…Moreover since c 2 R and c 2 T are constants, one can use the formula given in Eqs. (32), (34) and (27), namely…”
Section: B Models With F (φ) ∼ E µφmentioning
confidence: 99%
“…The study of NEC-violating cosmologies was initiated in [17]; they are often singular [see [18] [19] for more recent references discussing the singular case], but the fact that they can be non-singular and asymptotically locally de Sitter was pointed out in [20], and this observation has been developed in various ways in [21] [22][23] [24][25] [26]. "Phantom cosmologies" involving true violations of the NEC encounter well-known objections [27], but these are avoided by more sophisticated models in which the violation is merely effective 2 : for example, in brane-world theories [29] [30], or through quantum effects [31] [32], or by considering string-motivated Gauss-Bonnet corrections [33] to the Einstein-Hilbert Lagrangian. String theory apparently permits true NEC violation in the very early Universe; specifically, there are in fact explicit NECviolating cosmologies which have been constructed within string theory: Kachru and McAllister [34] have given such an example in the context of a warped deformed conifold in a Calabi-Yau compactification of II B string theory 3 .…”
Section: String Gases Topology and The Null Energy Conditionmentioning
confidence: 99%